Identifikasi Tantangan Serta Srategi Penyelesaian Pendidikan di Sekolah Dasar - Alifia Nur Zahra; Akmal Rais; Ido Yoseptian Simbolon; Maya Sari Siregar; Sio Oktaviana Siahaan (Lembag, 2024)
This study aims to identify hand-held challenges faced in education in primary schools and national education challenges. Education in Indonesia still revolves around educational problems that need to be elaborated in an effort to find answers to future challenges. Educational problems, causing the achievement of educational goals are not achieved optimally. In dealing with these problems, there needs to be an actional effort regarding the implementation of the curriculum in accordance with the characteristics of students and the equitable distribution of facilities / infrastructure in elementary school education. The research method uses a descriptive qualitative approach to paint a comprehensive picture of the challenges faced in education in primary schools. Where the data display technique used is in SD Negeri 060877 for female students, especially grade IV and V students totaling 27 students. The conclusion of the results of this study is that educational problems in elementary schools include :P the development of students, students' difficulties in mingling, unstable student emotions, students' mindset and individual differences in students such as students' learning speed that is still lagging behind compared to other friends, students who tend to be passive (quiet) and language skills of some students who are still lacking.